Spillovers through backward linkages from multinationals: measurement matters! - Salvador Barrios Cobos; Holger Görg; Eric Strobl (Institute for the Study of Labor (IZA), 2009)
We argue that the measures of backward linkages used in recent papers on spillovers from multinational companies are potentially problematic, as they depend on a number of restrictive assumptions, namely that (i) multinationals use domestically produced inputs in the same proportion as imported inputs, (ii) multinationals have the same input sourcing behaviour as domestic firms, irrespective of their country of origin, and (iii) the demand for locally produced inputs by multinationals is proportional to their share of locally produced output. We discuss why these assumptions are likely to be violated in practice, and provide alternative measures that overcome these drawbacks. Our results, using plant level data for Ireland, show clearly that the choice of backward linkage measure and thus, the assumptions behind them, matters greatly in order to draw possible conclusions regarding the existence of FDI-related spillovers. Using the standard measure employed in the literature we fail to find robust evidence for spillovers through backward linkages. However, when we use alternative measures of backward linkages that relax assumptions (i)-(iii), we find robust evidence for positive FDI backward spillover effects.
urn:nbn:de:101:1-20091019262
Keywords: F23; L22; 330; Multinationals; backward spillovers; productivity spillovers; Multinationales Unternehmen; Ausländisch; Lieferanten-Kunden-Beziehung; Produktivität; Spillover-Effekt; Messung; Irland